2019
DOI: 10.3390/jcm8050746
|View full text |Cite
|
Sign up to set email alerts
|

Computational Simulations Identify Pyrrolidine-2,3-Dione Derivatives as Novel Inhibitors of Cdk5/p25 Complex to Attenuate Alzheimer’s Pathology

Abstract: Mechanistically, neurotoxic insults provoke Ca2+-mediated calpain activation, which cleaves the cytoplasmic region of membrane-embedded p35 and produces its truncated form p25. Upon physical interaction, cyclin-dependent kinase 5 (Cdk5) and p25 forms hyperactivated Cdk5/p25 complex and causes severe neuropathological aberrations including hyperphosphorylated tau-mediated neurofibrillary tangles formation, Alzheimer’s symptoms, and neuronal death. Therefore, the inhibition of Cdk5/p25 complex may relieve p-tau-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Based on the RMSD plots, last 10 ns simulation trajectories were selected and a total of 40 snapshots were taken at a regular interval. The g_mmpbsa tool for GROMACS was employed to calculate the different parameters of binding free energies with the methodologies described in previous reports [46][47][48][49] .…”
Section: Binding Free Energy Calculationsmentioning
confidence: 99%
“…Based on the RMSD plots, last 10 ns simulation trajectories were selected and a total of 40 snapshots were taken at a regular interval. The g_mmpbsa tool for GROMACS was employed to calculate the different parameters of binding free energies with the methodologies described in previous reports [46][47][48][49] .…”
Section: Binding Free Energy Calculationsmentioning
confidence: 99%
“…Therefore, we argue that our pharmacophore model, generated with similar features as previous studies, gives reliable results for retrieving compounds that display a better binding affinity towards Hpse. The chosen Hpse pharmacophore model with the highest rank score was further validated by the decoy set validation method, generating a GF score of 0.72, which is near the ideal model range value of 1 ( Table 2 ) [ 53 , 54 , 55 ]. The validated model was, thus, considered to be robust for retrieving molecules from an external database, and therefore, the resultant model was allowed to screen the InterBioScreen database composed of natural (69,034) and synthetic (195,469) compounds ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found some new substrates and signaling pathways related to Cdk5 in AD, such asCdk5-Mcl-1axis (Nikhil and Shah, 2017 ), ALDH1A1 (Nikhil et al, 2019 ), miR-125b (Zhuang et al, 2020a ), and miR-504-3p (Chen et al, 2022 ). New Cdk5 inhibitors are also being studied in various AD models like pyrrolidine-2,3-dione, and TFP5 (Shukla et al, 2017 ; Zeb et al, 2019a , b ). It is also found that a traditional Chinese medicine, Nano-HO, improves cognitive function in AD by modulating the signaling pathway JNK/cdk5/GSK-3β (Qu et al, 2021 ).…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%